Analysis Factor of Compliance With Taking Anti-Pulmonary Tuberculosis Drugs in Patients With Pulmonary Tuberculosis - Vera Kurnia Putri; Chairil Zaman; Akhmad Dwi Priyanto; Dianita Ekawati (Lentera Perawat, 2025)
The most important factor of treatment compliance in the treatment of pulmonary tuberculosis patients is the patient's own awareness of their health status, thus ensuring treatment compliance and facilitating the achievement of recovery. This study aims to determine the description of the analysis of compliance with taking anti-pulmonary tuberculosis drugs in patients with pulmonary tuberculosis at the UPTD Puskesmas Nibung Kab. North Musi Rawas in 2024. This research design is quantitative cross sectional approach. The sample in this study amounted to 35 respondents. Respondent inclusion criteria are tuberculosis patients at UPTD Puskesmas Nibung Kab. North Musi Rawas and willing to become respondents. Data collection using a questionnaire. Bivariate data analysis using Chi-Square test and multivariate multiple logistic regression. The results showed the pvalue of each variable studied, namely gender p value 0.001, education (p value 0.008), occupation (p value 0.011), knowledge p value 0.000, family support p value 0.002, and attitude p value 0.001, on compliance with taking medication at the Nibung Health Center, North Musi Rawas Regency in 2024. The most dominant factor with drug compliance is gender (p value 0.001), (OR 15.583). The conclusion is that there is a significant relationship between gender, education, occupation, knowledge, family support and attitude towards adherence to taking medication. The health center should be able to provide counseling and education about tuberculosis and how to be obedient in taking anti-tuberculosis drugs.